Neuron-Specific Deletion of Scrib in Mice Leads to Neuroanatomical and Locomotor Deficits - Ezan, Jerome; Moreau, Maité M.; Mamo, Tamrat M.; Shimbo, Miki; Decroo, Maureen; Sans, Nathalie; Montcouquiol, Mireille (Frontiers in Genetics, 2022)
Scribble (Scrib) is a conserved polarity protein acting as a scaffold involved in multiple cellular and developmental processes. Recent evidence from our group indicates that Scrib is also essential for brain development as early global deletion of Scrib in the dorsal telencephalon induced cortical thickness reduction and alteration of interhemispheric connectivity. In addition, Scrib conditional knockout (cKO) mice have behavioral deficits such as locomotor activity impairment and memory alterations. Given Scrib broad expression in multiple cell types in the brain, we decided to determine the neuronal contribution of Scrib for these phenotypes. In the present study, we further investigate the function of Scrib specifically in excitatory neurons on the forebrain formation and the control of locomotor behavior. To do so, we generated a novel neuronal glutamatergic specific Scrib cKO mouse line called Nex-Scrib−/− cKO. Remarkably, cortical layering and commissures were impaired in these mice and reproduced to some extent the previously described phenotype in global Scrib cKO. In addition and in contrast to our previous results using Emx1-Scrib−/− cKO, the Nex-Scrib−/− cKO mutant mice exhibited significantly reduced locomotion. Altogether, the novel cKO model described in this study further highlights an essential role for Scrib in forebrain development and locomotor behavior.